2019
DOI: 10.14735/amko2019133
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Injury Induced by a Single Dose of Nivolumab – a Case Report and Literature Review

Abstract: Background: The use of nivolumab in the treatment of metastatic melanoma has become well established dur ing past years. Despite its undeniable efficacy, immune-related side effects may occur, includ ing acute liver injury. Liver toxicity caused by nivolumab is usually observed as liver enzyme elevation with mild or no symp toms; further, there is limited information regard ing any histopathological findings. Case: We report a case of a 38-year-old woman with metastatic melanoma who developed unusual nivolumab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 13 publications
0
9
0
1
Order By: Relevance
“…Our meta-analysis showed that, compared with standard chemotherapy, PD-1/PD-L1 inhibitor monotherapy and PD-1/PD-L1 inhibitor plus chemotherapy significantly increased the risk of all-grade and high-grade hepatitis. We found no descriptions of hepatitis in any of the trials that examined nivolumab, but some case reports indicated immune-related hepatitis after nivolumab treatment [35,40].…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Our meta-analysis showed that, compared with standard chemotherapy, PD-1/PD-L1 inhibitor monotherapy and PD-1/PD-L1 inhibitor plus chemotherapy significantly increased the risk of all-grade and high-grade hepatitis. We found no descriptions of hepatitis in any of the trials that examined nivolumab, but some case reports indicated immune-related hepatitis after nivolumab treatment [35,40].…”
Section: Discussionmentioning
confidence: 86%
“…Corticosteroid therapy is the mainstay of irAE management, although the response of immune-related liver injury to corticosteroid therapy can be variable. Kopecky et al [40] demonstrated a poor response to corticosteroid therapy when cholestatic hepatitis occurred in immune-mediated liver injury, and suggested use of a more potent immunosuppressive treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In these cases, a second immunosuppressive drug can be added, the most widely used being mycophenolate mofetil (MMF). 66,74,105,107,108,110,111 Azathioprine has also been used with success. 68,106 In a few clinical observations, the use of calcineurin inhibitors (cyclosporine and tacrolimus) has also been described as effective.…”
Section: Patients With Hepatitis Refractory To Corticosteroidsmentioning
confidence: 99%
“…Low-risk HPV types include types 6, 11, 42, 43, and 44. High-risk HPV types include types 16,18,31,33,34,35,39,45,51,52,56,58,59,66,68, and 70 [25,26]. Vaccines against HPV are essential to prevent the development of CC and other gynecologic cancers and to protect against HPV types 16 and 18.…”
Section: Risk Factors and Clinical Featuresmentioning
confidence: 99%
“…Currently, several clinical trials are assessing the clinical activity and safety of PD-L1 inhibitor monotherapy or in combination with chemotherapeutic agents such as bevacizumab, paclitaxel or carboplatin, cobimetinib (the mitogen-activated protein kinase enzymes inhibitor) [65], and platinum-based chemotherapy in OC (Table 4) [66,67]. The KGOG 3045 study aims to investigate durvalumab therapy in platinum-resistant recurrent OC patients [65,68]. In total, 68 patients have been randomized into four groups: group 1 will receive olaparib and cediranib, group 2 will receive olaparib and durvalumab, group 3 will receive durvalumab plus chemotherapy, and group 4 will receive durvalumab and tremelimumab plus chemotherapy.…”
Section: Monotherapy or Combination Therapy With Pd-l1 Inhibitors In mentioning
confidence: 99%